Six Points: A Plan for Success - Volker, John; Phillips, Michael (Journal of Management Policy and Practice, 2018)
We have struggled with the traditional business plan format and purpose for the last many years as academicians, consultants, and practitioners. The introduction of the business model canvas by Alex Osterwalder several years ago sent a shock wave through the entrepreneurial ecosystem and caused many to reconsider the role and need of the business plan. We submit that the business plan is a necessary component in the flow of idea to venture execution; just not in the cumbersome format that has made writing a business plan into an onerous task. We propose that the purpose of a business plan can be served and even enhanced with a concise depiction of critical elements that compose a successful venture. We offer a format for the business planning process that we term “The Six Point Business Plan”. Our business plan format offers the entrepreneur a means of exploring and elaborating on the nine areas developed using the business model canvas but avoids being a cumbersome chore. The Six Point Business Plan offers a dynamic means to present the essentials of the venture in the form of idea, resources, and execution.